Forging Islamic power and place : the legacy of Shaykh Daud bin ʻAbd Allah al-Fatani in Mecca and Southeast Asia - Bradley, Francis R. (Southeast Asia--politics, meaning, memory., 2016)
This work charts the nineteenth-century rise of a vast network of Islamic scholars stretching across Southeast Asia and the Indian Ocean to Arabia. Francis Bradley analyses the role of the vibrant Patani knowledge network in the formation of Islamic institutions of learning in Southeast Asia. He makes use of a range of sources, including official colonial documents, traveller accounts, missionary writings, and handwritten manuscripts.